New penta-saccharide-bearing tripod amphiphiles for membrane protein structure studies. Issue 20 (15th September 2017) - Ehsan, Muhammad; Ghani, Lubna; Du, Yang; Hariharan, Parameswaran; Mortensen, Jonas S.; Ribeiro, Orquidea; Hu, Hongli; Skiniotis, Georgios; Loland, Claus J.; Guan, Lan; Kobilka, Brian K.; Byrne, Bernadette; et al.
Abstract : A new penta-saccharide-bearing tripod amphiphile (TPS-E10L) conferred enhanced stability to β2 adrenergic receptor (β2 AR) and its Gs complex. Abstract : Integral membrane proteins either alone or as complexes carry out a range of key cellular functions. Detergents are indispensable tools in the isolation of membrane proteins from biological membranes for downstream studies. Although a large number of techniques and tools, including a wide variety of detergents, are available, purification and structural characterization of many membrane proteins remain challenging. In the current study, a new class of tripod amphiphiles bearing two different penta-saccharide head groups, designated TPSs, were developed and evaluated for their ability to extract and stabilize a range of diverse membrane proteins. Variations in the structures of the detergent head and tail groups allowed us to prepare three sets of the novel agents with distinctive structures. Some TPSs (TPS-A8 and TPS-E7) were efficient at extracting two proteins in a functional state while others (TPS-E8 and TPS-E10L) conferred marked stability to all membrane proteins (and membrane protein complexes) tested here compared to a conventional detergent. Use of TPS-E10L led to clear visualization of a receptor-Gs complex using electron microscopy, indicating profound potential in membrane protein research.